MANUFACTURE OF UREA - MELAMINE - FORMALDEHYDE GLUE USED FOR LAMINATED VENEER LUMBER PRODUCTION - Van Chu, Tran; Hien Mai, Trinh; Tuan Truong, Ly (Journal of Forestry Science and Technology, 2016)
In this study, glue Urea - Melamine- Formaldehyde (UMF) was created to produce laminated veneer lumber (LVL), then the quality of LVL produced from Urea-Formaldehyde glue (UF) of Gia Han Company was compared to that of LVL produced from UMF made in Laboratory of Wood Industry College, Vietnam National University of Forestry (VNUF). The research results show that: The technology of producing UMF glue and LVL is suitable with current production condition and can be well applied in Vietnam. This technological process has been tested and applied in production at some factories and enterprises in Vietnam. The UMF glue produced in this study was a good adhesive and met the requirements of a glue used for high-quality LVL production. The quality criteria of the UMF glue were much better than those of UF glue from Gia Han Company. Some quality criteria of LVL produced from the UMF reached the requirements of the standards CAN3 - 0437 - M85 and JAS S-11-15.2. The LVL produced from the UMF glue can be used for furniture and construction.